Economic impact of extending reflexed cryptococcal antigenaemia CD4 threshold in South Africa - Naseem Cassim; Lindi-Marie Coetzee; Manuel P. da Silva; Deborah K. Glencross; Wendy S. Stevens (Southern African Journal of HIV Medicine, 2024)
Background: Reflexed cryptococcal antigenaemia (CrAg) testing has been offered since 2016 in South Africa, on remnant CD4 specimens, for people with a count 100 cells/μL. Local guidelines recommended extending testing to 200 cells/μL.